Contributions of Women-Owned SMEs Entities to Economic Growth – A Case Study of Women-Led SMEs in Kilifi North Sub-County, Kilifi, Kenya - Shaban, Esha; Kilei, Pearly (International Journal of Research in Interdisciplinary Studies, 2024)
This study examines the impact of women-led small and medium enterprises (SMEs) on economic development in Kilifi County, Kenya. Despite the critical role of SMEs in economic growth, women entrepreneurs face unique challenges that hinder their success. The objectives were to assess the level of innovativeness, job creation, financial savings mobilization, and management efficiency among women-led SMEs. Utilizing a descriptive research design, the study employed both quantitative and qualitative methods, including questionnaires and case studies, to gather data from 160 women entrepreneurs. Major findings indicated that 40.5% of respondents believed that the development of new products or services is vital for business growth, while 34.9% recognized that innovation drives economic development. Additionally, 60.3% of women entrepreneurs were below 40 years of age, highlighting a youthful demographic in this sector. However, challenges such as limited access to training (45.2% do not save anything from their businesses) and financial resources were prevalent. The study concludes that empowering women entrepreneurs through targeted training, improved access to financial support, and enhanced networking opportunities is crucial for maximizing their contribution to economic development. Recommendations include establishing training programs to enhance skills, developing financial products tailored for women-led SMEs, and creating platforms for networking and mentorship to foster collaboration and support among women entrepreneurs. These measures can significantly enhance the sustainability and growth of women-led SMEs in Kilifi County, ultimately driving economic progress.